The Role of Mathematics in Artificial Intelligence and Its Applications - Meena, Krisn Pratap (International Journal on Orange Technologies, 2023)
Artificial intelligence (AI) is revolutionizing industries and our lives at an unprecedented rate, and mathematics plays a fundamental role in this progress. In this article, we explore the vital role of mathematics in AI, including the innovative contributions of mathematicians, the challenges they face, and the opportunities for applied mathematicians in this dynamic field.